E-Learning in Teaching Emergency Disaster Response Among Undergraduate Medical Students in Malaysia - Saiboon, Ismail M.; Zahari, Fareena; Isa, Hisham M.; Sabardin, Dazlin M.; Robertson, Colin E. (Frontiers in Public Health, 2021)
Introduction Teaching disaster response medicine (DRM) to medical students requires considerable resources. We evaluate the effectiveness of e-learning in teaching emergency disaster response (ELITE-DR), a novel initiative, in educating medical students of the cognitive aspect of DRM. Methods A prospective cross-sectional study among pre-clinical year medical students was carried out to determine their knowledge on DRM and perception regarding the ELITE-DR initiative using a validated online questionnaire. A three-part self-learning video covering the principles and medical management of DRM were distributed before answering the questionnaire served as the training. Results A total of 168 students participated in the study. Their overall knowledge showed a significant increase in between pre-and-post interventions. Recall and simple decision-making knowledge aspects were better than complex decision-making knowledge. It appeared that participants assimilate knowledge better from visual rather than audio stimuli. Participants with high perception-scores demonstrated better knowledge-scores. However, e-learning was not preferred as a substitute for face-to-face (F2F) teaching. Conclusion ELITE-DR shows promise in teaching DRM. Simple recall and comprehension levels of knowledge were well-served through this technique. However, for more complex decision-making knowledge, a different approach might be required. ELITE-DR offers flexibility, accessibility, and personalized learning. The content presentation is improved by using several different visual stimuli. This approach is useful for cognitive aspect learning, but it should not replace standard F2F teaching.